2015
DOI: 10.1039/c5ra15022a
|View full text |Cite
|
Sign up to set email alerts
|

Carbon@NiCo2S4 nanorods: an excellent electrode material for supercapacitors

Abstract: Carbon@NiCo2S4 nanorods were synthesized through a facile in situ hydrothermal approach using carbon supported nickel (Ni/C) nanorods as both the template and nickel source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…It is clearly demonstrated that the NPHG-8 electrode has high current density and lower onset potential than that of Pt/C (Figure 3d). These results are consistent with the previous reports of core-shell N,P,O co-doped carbon nanoparticles, [24] Ocontaining (e. g., quinone group [25] ) carbon, and pyridinic N doped graphene. Rotating ring-disk electrode (RRDE) voltammograms of the NPHG-8 at 1600 rpm (Figure 3f) indicate an electron transfer number (n) of ca.…”
Section: N P Co-doped Hierarchical Porous Graphene As a Metal-free Bsupporting
confidence: 93%
See 1 more Smart Citation
“…It is clearly demonstrated that the NPHG-8 electrode has high current density and lower onset potential than that of Pt/C (Figure 3d). These results are consistent with the previous reports of core-shell N,P,O co-doped carbon nanoparticles, [24] Ocontaining (e. g., quinone group [25] ) carbon, and pyridinic N doped graphene. Rotating ring-disk electrode (RRDE) voltammograms of the NPHG-8 at 1600 rpm (Figure 3f) indicate an electron transfer number (n) of ca.…”
Section: N P Co-doped Hierarchical Porous Graphene As a Metal-free Bsupporting
confidence: 93%
“…2.8-2.9 per oxygen molecular in a wide potential range, suggesting a mixed two-and four-electron ORR pathway. These results are consistent with the previous reports of core-shell N,P,O co-doped carbon nanoparticles, [24] Ocontaining (e. g., quinone group [25] ) carbon, and pyridinic N doped graphene. [26] Finally, a possible mechanism for ORR and OER on N, P codoped graphene has been proposed, which follow the model proposed by Suen et al [27] (Scheme 2).…”
Section: N P Co-doped Hierarchical Porous Graphene As a Metal-free Bsupporting
confidence: 93%
“…Besides, the electrical double layer on the surface of S, N-doped carbon could also contribute the specific capacitance in a way. 29,53 Teng and co-workers recently reported that the introduction of Ni species into carbon matrix can impart the carbon material with a surface polarity, thus enhancing dipole affinity towards OHand improving surface wettability of carbon material favourable for facilitating ion diffusion and increasing the ion-accessible surface area for high capacitance. 54 As shown in Fig.…”
Section: Electrochemical Performancementioning
confidence: 99%
“…This is because, owing to their relatively small band gap, they offer greater electrochemical activity and capacity than mono-metal sulphides. [11][12][13][14][15][16][17][18] To tune the electrical activity and performance of such materials, many researchers have applied numerous synthetic strategies to obtain various morphologies. [19][20][21][22][23][24][25] Various metal sulphides have been synthesized using hydrothermal, electrodeposition, precipitation, sol-gel, electrospinning, and solution-based methods.…”
Section: Introductionmentioning
confidence: 99%
“…One effective approach involves wrapping the metal sulphides with a carbon layer, which enhances the electrical conductivity of the composite and preserves its structural integrity. 11,14,24,26 Layered carbon, which offers electrical conductivity and a large surface area, can be coupled with inorganic materials and utilized as a perfect matrix. This endows the nanohybrids with unique structural characteristics and synergistically enhanced electrochemical properties that are derived from both counterparts.…”
Section: Introductionmentioning
confidence: 99%